Dietary exposure of general Chinese population to fatty acid esters of 3-monochloropropane-1, 2-diol (3-MCPD) from edible oils and oil-containing foods. Issue 1 (2nd January 2021) - Cui, Xia; Zhang, Lei; Zhou, Pingping; Liu, Zhaoping; Fan, Sai; Yang, Dajin; Li, Jianwen; Liu, Qing
ABSTRACT: Edible oils and oil-containing foods have been regarded as the main source of 3-monochloropropane-1, 2-diol (3-MCPD) esters. A total of 3, 847 individual food samples were collected in China to carry out 3-MCPD fatty acid esters analysis. The samples comprising edible oils, fried foods and bakery foods from 31 Chinese provinces, municipalities and autonomous regions were obtained from the national food contaminant information system during 2015–2017. The dietary exposure and potential risks associated with the consumption of 3-MPCD esters from edible oils and oil-containing foods were estimated using a semi-probabilistic assessment model. Concentrations of 3-MCPD fatty acid esters in food samples were detected by gas chromatography-mass spectrometry (GC-MS). The mean levels of 3-MCPD fatty acid esters in edible oils, fried foods and bakery foods were 0.862, 0.249 and 0.145 mg/kg, respectively. The range of mean dietary intakes of 3-MCPD esters in different subpopulation groups (classified by gender and age) was from 0.586 to 1.539 μg/kg bw/day, which were all lower than 2 μg/kg bw/day – the tolerable daily intake (TDI) established by the European Food Safety Authority (EFSA). The range of dietary intake of 3-MCPD esters in high consumers (95th percentile) in each group was from 1.511 to 4.027 μg/kg bw/day, which accounted for 75.6% to 201.4% of the TDI. The 3-MCPD esters exposure level of 3.5% of the total Chinese population exceeded the TDI. The findings indicate that the potential health risks caused by dietary 3-MCPD esters from edible oils and oil-containing foods were of low concern for most of the Chinese population. However, the exposure risk of the consumers with excessive edible oil consumption calls for attention. Graphical Abstract: uf0001